Proteomics of human cerebral microdialysate: from detection of biomarkers to clinical application - Maurer, Martin H.; Haux-Nettesheim, Daniel; Unterberg, Andreas; Sakowitz, Oliver (Proteomics. Clinical applications, 2008)
Cerebral microdialysis is applied in clinical neurology and neurosurgery as monitoring tool in patients to evaluate the progression of severe diseases, such as stroke or trauma. Besides small molecules, e.g. metabolites and neurotransmitters, also the macromolecules, such as proteins and larger chemical compounds cross the dialysis membrane of the catheters implanted into the human brain parenchyma. Microdialysis can be used to extract molecules from the extracellular space of the brain in vivo, but additionally to deliver drugs, since the exchange is dependent on concentration gradients. Cerebral microdialysis may also be useful in the prediction of the clinical onset of symptoms, based on changes in the composition of pre-symptomatic microdialysate. For example, symptomatic vasospasm, which is a complication after subarachnoid hemorrhage, may be predicted by the combination of cerebral microdialysis and a proteomics approach. We will introduce the basic concepts of cerebral microdialysis, discuss possible clinical applications, and evaluate the application of proteomic approaches. With regard to technological aspects, we describe two-dimensional gel electrophoresis, high-pressure liquid chromatography, and mass spectrometry. With regard to clinical aspects, we discuss ethics, feasibility, time-course, and therapeutic options. In conclusion, proteomics of cerebral microdialysate may be used for diagnosis, disease monitoring, and therapeutic intervention of neurological patients.